Feeling the (post)colonial: Affective encounters and enduring regimes of territorialization along the Kokoda Track, Papua New Guinea. (13th January 2023) - Stead, Victoria
Abstract: The Kokoda Track, which spans Papua New Guinea's Oro and Central Provinces, has become a site of profound Australian national feeling. Each year, thousands of Australian trekkers travel to Papua New Guinea to "do" the 96‐km hiking trail, in remembrance of the battle waged along it during the Second World War. For Oro Province people, meanwhile, Kokoda—denoting both the track and the place where the track commences—is also a site of intense feeling, albeit in ways that are both less mythologized and less amenable to mythologization. Attending to these divergent affective experiences highlights affect as a domain of postcolonial encounter. Affect works to reproduce colonial relations and animate ongoing regimes of territorialization. It does so while deflecting Australians' attention away from the very colonial contexts within which affect is implicated. At the same time, uneven geographies of affect index complexities of Papua New Guinean feeling that exceed those sanctioned within the confines of the trekking industry itself.